Tumor-intrinsic CD21 expression impacts the response of B-cell malignancy cells to CD19-CAR-T cells. Issue 4 (25th March 2022) - Li, Dan; Xu, Qiongyu; Hu, Yutian; Wang, Wenbing; Xie, Shufeng; Zhao, Chunjun; Liu, Han
Abstract: CD19-chimeric antigen receptor (CAR)-based T-cell therapy has produced promising clinical responses in patients with relapsed or refractory B-cell malignancies. However, a significant portion of patients with mature B cell-derived malignancies, including chronic lymphocytic leukemia (CLL) and non-Hodgkin's lymphoma (NHL), do not respond to CD19-CAR-T cell therapy. Whether any characteristics and biomarkers intrinsic to cancer cells themselves can predict the CD19-CAR-T cell therapeutic response remains largely unknown. Surprisingly, by using experimental models, we show here that malignant B cells bearing CD21, a mature B cell marker, could not be efficiently killed by CD19-CAR-T cells. CD19, CD21, and CD81, together with CD225, form the B cell coreceptor complex that enhances B cell-mediated signaling. Our results indicated that CD21 affected the recognition of CD19-positive tumor cells by CD19-CAR-T cells and impaired the antitumor capacities of these effector cells. We have not only uncovered a mechanism underlying the impairment of CD19-CAR-T cells in mature B cell-derived CLL and NHL, but also proposed a pretreatment biomarker that may predict CD19-CAR-T cell therapeutic response, thus preventing foreseeable therapy failure and suggesting optimal personized therapies. Graphical Abstract: Tumor-intrinsic CD21 impairs the target cell recognition and the cytotoxicity of the CD19-CAR-T cells.